Downregulation of Candidate Gene Expression and Neuroprotection by Piperine in Streptozotocin-Induced Hyperglycemia and Memory Impairment in Rats - Kumar, Suresh; Chowdhury, Suman; Razdan, Ajay; Kumari, Deepa; Purty, Ram Singh; Ram, Heera; Kumar, Pramod; Nayak, Prasunpriya; Shukla, Sunil Dutt (Frontiers in Pharmacology, 2021)
There are accumulating evidence showing that hyperglycaemic conditions like diabetes possess a greater risk of impairment to the neuronal system because high glucose levels exacerbate oxidative stress, accumulation of amyloid-beta peptides, mitochondrial dysfunction, impair cognitive functions, and causes neurodegeneration condition like Alzheimer’s diseases. Due to the extensive focus on pharmacological intervention to prevent neuronal cell impairment induced by hyperglycemia, the underlying molecular mechanism that links between Diabetes and Alzheimer's is still lacking. Given this, the present study aimed to evaluate the protective effect of piperine on streptozotocin (STZ) induced hyperglycemia and candidate gene expression. In the present study, rats were divided into four groups: control (Vehicle only), diabetic control (STZ only), piperine treated (20 mg/kg day, i.p), and sitagliptin (Positive control) treated. The memory function was assessed by Morris water maze and probe test. After treatment, biochemical parameters such as HOMA index and lipid profile were estimated in the serum, whereas histopathology was evaluated in pancreatic and brain tissue samples. Gene expression studies were done by real-time PCR technique. Present data indicated that piperine caused significant memory improvement as compared to diabetic (STZ) control. The assessment of HOMA indices in serum samples showed piperine and sitagliptin (positive control, PC) caused significant alterations of insulin resistance, β cell function, and insulin sensitivity. Assessment of brain and pancreas histopathology shows significant improvement in tissue architecture in piperine and sitagliptin treated groups compared to diabetic control. Gene expression profile in brain tissue shows significantly reduced BACE1, PSEN1, APAF1, CASPASE3, and CATALASE genes in the piperine and sitagliptin (PC) treated groups compared to Diabetic (STZ) control. The present study demonstrated that piperine not only improves memory in diabetic rats but also reduce the expression of specific AD-related genes that can help design a novel strategy for therapeutic intervention at the molecular level.